Vietnam trade with EU and UK after free trade agreements and three years of COVID-19 (International Journal of Scientific Research and Management (IJSRM), 2023)
The European Union-Vietnam Free Trade Agreement (EVFTA), taking effect on August 2020, was expected to bring strategic benefits for Vietnam with one of its largest and most important partners. However, the United Kingdom, a leading economy within the EU, was left the EU on the January of the same year. The new free trade aggrement between UK and Vietnam, known as UKVFTA, was signed with the hope to avoid missing any benefits that the EVFTA had promised. This paper aims to identify and analyze the impact of the two aggrements, EVFTA and UKFTA on Vietnam-EU’s and Vietnam-UK trades under the negative effects of the Covid-19 pandemic. A compehensive analysis of the trade between Vietnam and the two mentioned partners for two year before and two year after the agrrement was made to carry out the positive effects of the contracts. The secondary data were taken from the World Bank, ADB and Vietnam Office of Statistics. The results showed that, the two aggrements successfully brought about higher surpluses for Vietnam trade, despite the fact that the overall of Vietnam trade are mostly deficit during the four examined years. The results would be helpful to evaluate free trade agreements for overcoming the negative impact of the Covid-19 pandemic for Vietnam and other developing countries.